Levantamento de maturidade em gerenciamento de portf??lio de projetos em organiza????es da Administra????o P??blica Federal - Oliveira, Roosevelt Benvindo de (2017)
Adopting good project portf??lio management practices benefits private and public organizations by prioritizing and aligning projects with organizational strategy. In this sense, over the last decades, codes of best practices have been launched in project portf??lio management that gather recommendations on the theme. This research project aims to develop a survey of the maturity of project portf??lio management focusing on the Federal Public Administration (APF) agencies, through the adoption of best practice guidelines with emphasis on the Management System Project Portf??lio Management Methodology of Information Technology Resources (MGPP - SISP), under the Ministry of Planning Budget and Management (MPOG). For this, the technical procedures used in this research were content analysis, application of online questionnaire and analysis of data collected. Content analysis allowed the organization of the six dimensions of the maturity model proposed by Almeida (2015) in objective questions to evaluate the maturity levels in each dimension. The application of the model was performed through the online survey, which had the participation of Federal Public Administration bodies. The data analyzes showed that, in general, there is a low maturity of the organs surveyed in project portf??lio management. The research contributes to the understanding of the current situation of maturity in project portf??lio management of public organizations and can serve as a reference for future comparisons and support to improve maturity in project portf??lio management practices and consequent improvement of public governance.